Visual Merchandising, Celebrity Endorsers, Advertisement Creativity, and E-Service Quality on Netflix Purchase Decision - Mardani, Wilda Ayu Putri; Krisnawati, Wenti (Interdisciplinary Social Studies, 2022)
Background: Advances in technology are not foreign to us. Over time, technology is growing rapidly and rapidly, making it easier for people to access and utilize technology. The development of technology, especially in the field of information, has an impact on several sectors of life, including the economic, social, and cultural sectors. Aim: This research aims to find out the influence of Visual Merchandising, Celebrity endorsers, ad creativity, and E-service Quality on the purchase of the Netflix video streaming app. Method: Using 100 respondents as a sample. The study used multiple linear regression analysis using four hypotheses. Test the hypothesis using the t-test with a signification level of 0.05. Findings: The calculation results showed that the free variables namely Visual Merchandising, Celebrity Endorser, Creative Advertising, and E-Service Quality partially positively affected the purchase number with signification numbers below 0.05. Based on the results of the analysis, it is expected that Netflix can improve Visual Merchandising, Celebrity Endorser, advertising creativity, and E-service Quality. This will increase the number of purchases of the Netflix video streaming app.